2009
DOI: 10.1021/ar900036b
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Design of Antimicrobial Polymers, Foldamers, and Small Molecules: From Discovery to Practical Applications

Abstract: Conspectus Antimicrobial peptides (AMPs) provide protection against a variety of pathogenic bacteria and are, therefore, an important part of the innate immune system. Over the last decade, there has been considerable interest in developing AMPs as intravenously administered antibiotics. However, despite extensive efforts in the pharmaceutical and biotechnology industry, it has proven difficult to achieve this goal. While researchers have solved some relatively simple problems such as susceptibility to proteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
397
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(403 citation statements)
references
References 106 publications
5
397
0
1
Order By: Relevance
“…Therapeutic use of some synthetic versions of AMPS is being actively explored with the aim of optimizing efficacy while minimizing the limitations of endogenous AMPs (Rozgony et al, 2009;Tew et al, 2010). Because of the complexity of the vertebrate immune system, however, use of synthetic AMPS as antimicrobial agents will need to be carefully tested to ensure that such treatments do not result in negative unforeseen impacts on the host's immune response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic use of some synthetic versions of AMPS is being actively explored with the aim of optimizing efficacy while minimizing the limitations of endogenous AMPs (Rozgony et al, 2009;Tew et al, 2010). Because of the complexity of the vertebrate immune system, however, use of synthetic AMPS as antimicrobial agents will need to be carefully tested to ensure that such treatments do not result in negative unforeseen impacts on the host's immune response.…”
Section: Resultsmentioning
confidence: 99%
“…These include bioavailability (limited tissue distribution), stability, potential immunogenicity, potential eukaryotic toxicity, and high production costs (Liu et al, 2010;Rotem & Mor, 2009;Tew et al, 2010). Many laboratories are developing synthetic AMPs and peptidomimetics in an attempt to overcome these limitations of natural AMPs while maximizing the antimicrobial effects.…”
Section: Endogenous Amps: Amps Of Eukaryotic Originsmentioning
confidence: 99%
“…[1][2][3][4][5] A foldamer can be defined as "a discrete oligomer that folds into a conformationally ordered state in solution", and contemporary research has shown that a number of foldamer constructs (in particular, antimicrobial peptides (AMPs)) can interact with, and disrupt, bacterial cell membranes thus making these agents valid candidates for future therapeutics, particularly if selectivity over host cells can be achieved. [6][7][8][9][10][11][12][13][14] In light of this need, our research group has recently developed a range of AMP-influenced mimetics which are based on a foldamer scaffold, under the presumption that control over antimicrobial properties could be obtained by fine-tuning the molecules' charge, amphiphilicity and conformation. 8,[10][11][12][13][15][16][17][18][19] Previous efforts have looked at the influence of foldamer length and conformation on membrane interaction, [15][16][17][18][19] but as yet, the effects of charge and thereby amphiphilicity have not been studied against bacterial membranes by us.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the appearance of "superbugs", which are resistant to almost all commercial antibiotics, has been a critical worldwide healthcare issue [2,3]. As a result, developing new classes of efficient antimicrobial agents has been the focus of significant research efforts during the last decade [4][5][6][7][8][9]. Since the discovery of the antimicrobial properties of poly(phenylene ethynylene) (PPE)-based cationic conjugated polyelectrolytes (CPEs) [10], a wide range of structurally similar polymeric CPEs and oligomeric OPEs (oligo-phenylene ethynylenes) have been synthesized [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%